ASESMEN KOMPETENSI MINIMUM (AKM) DAN SURVEI KARAKTER PADA SMA NEGERI 9 BANDA ACEH DAN SMK NEGERI 1 BANDA ACEH - Ratih Ayu Wandira; Ismail Ismail; Irma Anggraini (Jurnal Economica Didactica, 2022)
This study aims to determine the Minimum Competency Assessment (AKM) and Character Survey at SMA Negeri 9 Banda Aceh and SMK Negeri 1 Banda Aceh. The approach used in this research is a quantitative approach with descriptive research type. The population in this study were all students of class XI SMA Negeri 9 Banda Aceh totaling 184 people and class XI students of SMK Negeri 1 Banda Aceh totaling 259 people. Meanwhile, the samples in this study were students of class XI SMA Negeri 9 Banda Aceh and class XI SMK Negeri 1 Banda Aceh which were designated by the Ministry of Education and Culture as participants in the national assessment, totaling 50 people. Data was collected through observation and distributing questionnaires. Based on the results of the research conducted, the results obtained that the Minimum Competency Assessment (AKM) at SMA Negeri 9 Banda Aceh obtained an achievement rate of 80.06%. While the Minimum Competency Assessment (AKM) at SMK Negeri 1 Banda Aceh obtained an achievement rate of 79.30%. Under these conditions, the results of the study indicate that the Minimum Competency Assessment (AKM) at SMA Negeri 9 Banda Aceh has been carried out well, while the Minimum Competency Assessment (AKM) at SMK Negeri 1 Banda Aceh has been carried out quite well. The results of the research for the Character Survey at SMA Negeri 9 Banda Aceh obtained an achievement rate of 78.48%. While the Character Survey at SMK Negeri 1 Banda Aceh obtained an achievement rate of 86.67%. With these conditions, the results of the study indicate that the Character Survey at SMA Negeri 9 Banda Aceh has been carried out quite well, while the Character Survey at SMK Negeri 1 Banda Aceh has been carried out well. The results of the research for the National Assessment at SMA Negeri 9 Banda Aceh obtained an achievement rate of 85.10%. Meanwhile, the National Assessment at SMK Negeri 1 Banda Aceh obtained an achievement rate of 81.46%. Under these conditions, the results of the study indicate that the National Assessment at SMA Negeri 9 Banda Aceh and SMK Negeri 1 Banda Aceh has been carried out properly.